Comment on “Effect of Acupuncture Intervention on Chronic Musculoskeletal Pain in Hemodialysis-Dependent Kidney Failure Patients: Study Protocol for a Randomized Controlled Clinical Trial” [Letter] - He L; Lv S (Journal of Pain Research)
Linli He, Shibei Lv The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of ChinaCorrespondence: Shibei Lv, The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China, Email lvbb9946@163.com